CASE REPORT PROGRESSIVE LWER LIMB PARAPLEGIA IN PREGNANCY - AN AGRESSIVE VERTEBRAL HAEMANGIOMA (Bombay Hospital Journal, 2026)
We present a rare case of spinal cord haemangioma in a pregnancy at 38 weeks of gestation, managed with multidisciplinary approach. The patient presented with back pain and neurological symptoms, diagnosed via MRI. Successful management involve close monitoring, pain control and planned delivery. This case heighlights the importance of prompt diagnosis and collaborative cae in ensuring optimal outcome for both mother and baby